Question about The Learning Company Achieve! Math & Science Grades 1-3 (381933) for PC, Mac

1 Answer

-4(x-2) 3(-4-x) Who Do you solve this?

Posted by on

1 Answer

  • Level 2:

    An expert who has achieved level 2 by getting 100 points

    MVP:

    An expert that gotĀ 5 achievements.

    Vice President:

    An expert whose answer gotĀ voted for 100 times.

    Novelist:

    An expert who has written 50 answers of more than 400 characters.

  • Expert
  • 185 Answers

Hi blackeyedbab:

Something is missing here. In order to "solve" this, there has to be an equal sign somewhere.

My educated guess is:

#1 -4(x-2) = 3(-4-x) in which case the solution is (removing parentheses)
-4x + 8 = -12 - 3x or -x = -20 or x = 20

Hope this helps... Loringh PS Please leave a rating if appropriate Thks

Posted on Nov 20, 2008

Add Your Answer

Uploading: 0%

my-video-file.mp4

Complete. Click "Add" to insert your video. Add

×

Loading...
Loading...

Related Questions:

1 Answer

What is gapesa


G- given A- asked P-process E-equation S-solve A-answer
an anagram of the process used to solve certain problems such as algebra etc.

Aug 21, 2016 | The Learning Company Achieve! Math &...

2 Answers

What are the x and y intercepts of -x +7y = 12 ?


You can't solve this. When you have two unknowns you need two equations to solve it and not -10x + 70y = 120, because that is the same equation.
If you know the value of x, or from y you also could solve it.

Jan 23, 2015 | Educational & Reference Software

1 Answer

How can i get some solved essay ?


that's a big fact . to write a clear essay you have to know something . hardly you get some solved essay . if you need a solved essay you have to go some websites . i think you also need to know some rules to bye them . if you need some clear essay you have to go this link
Talented Essay Writers Only

Mar 22, 2014 | Educational & Reference Software

1 Answer

Professor Layton Miracle Mask puzzle no 61 cant solve it doesnt add up


You seem to believe that any person who reads your question has that Professor Layton Miracle Mask Puzzle available. It ain't so. What you can do is spell out the puzzle in your post. Maybe someone will solve it.

Nov 27, 2013 | Nintendo Professor Layton Miracle Mask

1 Answer

Need help in knowing how to solve 6x^4-6y^4


These other forms might help you solving your problem!


gif&s=25&w=69&h=22

gif&s=25&w=159&h=22
I hope this helps you solving this math problem!

With kind regards,

MisterN

Aug 10, 2011 | Mathsoft StudyWorks! Mathematics Deluxe...

2 Answers

Write each quadratic equation in standard form. . identify the values of a,b,and c. . ...


  • Solve (x + 2)(x + 3) = 12.
    It is very common for students to see this type of problem, and say:
      "Cool! It's already factored! So I'll set the factors equal to 12 and
      solve to get x = 10 and x = 9. That was easy!"

    Yeah, it was easy; it was also (warning!) wrong. Besides the fact that (10 + 2)(9 + 3) does not equal 12, you should never forget that you must have "(quadratic) equals (zero)" before you can solve.
    So, tempting though it may be, I cannot set each of the factors above equal to the other side of the equation and "solve". Instead, I first have to multiply out and simplify the left-hand side, then subtract the 12 over to the left-hand side, and re-factor. Only then can I solve.
      (x + 2)(x + 3) = 12
      x2 + 5x + 6 = 12
      x2 + 5x - 6 = 0
      (x + 6)(x - 1) = 0
      x + 6 = 0 or x - 1 = 0
      x = -6 or x = 1
    Then the solution to (x + 2)(x + 3) = 12 is x = -6, 1

Jul 17, 2011 | H. B. Enterprises Quadratic Solver

1 Answer

Need help in Algerbra, how to solve this problem 3(8)+3(5+3)=_x(10+2)


3(8)+3(5+3)=x(10+2) First add numbers in ()
3(8)+3(8)=x(12) Now multiply the numbers next to ()
24+24=12x Now add the 24 +24
48=12x Now we have to solve for x. 12x is actually 12 times x. in order to solve for x we have to do the opposite and divide by 12
48=12x
12 12

4=1x is the same as 4=x.

Mar 26, 2010 | Mathsoft Solving and Optimization...

1 Answer

Solve g(x)=-x


Simplifying
g(x) = -1x

Multiply g * x
gx = -1x

Solving
gx = -1x

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Divide each side by 'x'.
g = -1

Simplifying
g = -1

Jan 21, 2010 | SoftMath Algebrator - Algebra Homework...

1 Answer

Program not running


Have you solved this problem? The same thing is happening to me , if you have any answers could you email me brett@ijewellery.com.au

Mar 22, 2009 | Dk Multimedia My First Incredible Amazing...

3 Answers

Solving systems of equations by elimination


Hi joanmae jmeh;

You can add these equations just like you would numbers

3x + 2y = 7
5x - 2y = 1
-----------------------
8x =8
x=1
Now plug x = 1 back into either equation and you can solve for y
Y = 2

When you add the 2 equations together the +2y and the -2y cancel
out

Hope this helps Loringh Please leave a rating for me Thks

Dec 01, 2008 | Bagatrix Algebra Solved! 2005 (105101) for...

Not finding what you are looking for?
The Learning Company Achieve! Math & Science Grades 1-3 (381933) for PC, Mac Logo

Related Topics:

153 people viewed this question

Ask a Question

Usually answered in minutes!

Top The Learning Company Educational & Reference Software Experts

k24674

Level 3 Expert

7987 Answers

Stitch85

Level 1 Expert

22 Answers

lbrewer42
lbrewer42

Level 1 Expert

9 Answers

Are you a The Learning Company Educational and Reference Software Expert? Answer questions, earn points and help others

Answer questions

Manuals & User Guides

Loading...